PERTUMBUHAN TANAMAN MARASI (Curculigo latifolia) DENGAN PERBEDAAN KONSENTRASI NAA (Naphthalene Acetic Acid) DAN BAP (Benzyl Amino Purine) SECARA IN VITRO - Mohamad Ana Syabana; Imas Rohmawati; Endah Pamuji Ningsih (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2015)
The aim of this research was to know In Vitro initiation on shoots of marasi (Curculigo latifolia) by different concentration of NAA(Naphthalene Acetic Acid) And BAP (Benzyl Amino Purine). This research has been done at Biotechnology Laboratory of Agriculture Faculty, Sultan Ageng Tirtayasa University since August to October 2014. This research used Randomized Complete Design (RCD) with two factors. The first factor was NAA concentration with 4 levels, they were mg/l; 0,2 mg/l; 0,4 mg/l; 0,6 mg/l. The second factor was BAP concentration with 4 levels, they were 0 mg/l; 0,5 mg/l; 1 mg/l; 1,5 mg/l. The research showed that the NAA concentration gave significant effect on plant height at 4, 5, 6 and 7 WAP (Week after planting), and the BAP concentration gave significant effect on plant height at 7 WAP. There were not combination effect on NAA and BAP concentration on bud initiation time and plant height. All the living explants during the observation reached 83,5% with the number of contaminating explants was 60% and browning explants 87,5%.